Improvement of engine performance of a single-cylinder compression ignition engine using 3D-printed helical thread intake manifold - Hairuddin, Abdul Aziz; Shafanejad, Mohammed Amin (Centre for Advanced Research on Energy, Faculty of Mechanical Engineering, Universiti Teknikal Malaysia Melaka, 2018)
Over past decades different types of intake manifolds had been introduced but there are limited literatures about the behavior of helical threaded intake manifold with a clear classification. This study emphasis of the comparison for performance of a single cylinder engine with three different intake manifolds. The manifolds (trapezoidal and circular) have been printed by using 3D-printer to the engine parameters such as torque, emission level, power output and specific fuel consumption. The highest value of torque is 11.6 Nm at 1500 rpm which belongs to circular threaded intake manifold. The NOX emission level for trapezoid threaded intake manifold in overall is lower than other two intake manifolds. The CO emission level for circular threaded intake manifold is slightly higher than the trapezoidal threaded intake manifold meanwhile the current intake manifold has the highest CO emission level. The highest power output belongs to circular threaded intake manifold at 3030 W. Circular threaded intake manifolds is good to be investigated for future studies.